2021
DOI: 10.18393/ejss.930620
|View full text |Cite
|
Sign up to set email alerts
|

Compressibility behaviour and engineering properties of North Borneo Peat Soil

Abstract: Article InfoIt is known that peat soil is highly compressible. A constituent of peat soil from Klias, Sabah covering a wide range of index properties of fiber contents, specific gravity, organic contents and moisture contents were subjected to one-dimensional consolidation tests. This paper presents the engineering properties and compressibility behavior of sapric type of tropical peat soil. In this role, the high compressibility of Klias peat stands out as a most significant engineering property. With this in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
2
5
1
Order By: Relevance
“…Additionally, based on the von Post criteria, the Klias peat soil was classified as hemic peat (H6). The natural moisture content obtained was 657%, within the range of previously published values for peat originating from Klias, Beaufort, and Sabah [58,59]. The organic content was valued at 96.57%, and conventional values of organic content for peat soils from East Malaysia are within the range of 50-98% [1].…”
Section: Physical Propertiessupporting
confidence: 77%
“…Additionally, based on the von Post criteria, the Klias peat soil was classified as hemic peat (H6). The natural moisture content obtained was 657%, within the range of previously published values for peat originating from Klias, Beaufort, and Sabah [58,59]. The organic content was valued at 96.57%, and conventional values of organic content for peat soils from East Malaysia are within the range of 50-98% [1].…”
Section: Physical Propertiessupporting
confidence: 77%
“…Muscovite is a hydrated phyllosilicate mineral of aluminium and potassium with formula KAl₂(F, OH)₂ and identified as mineral of the mica family. It is an important rock-forming mineral which is appeared less resistant to micro-organism weathering than biotite and the latter less than orthoclase [33][34][35]. This finding clearly shows that the crystallization process between peat and EPP contributes to the development of compact structure and filled micro spaces or void in peat soil.…”
Section: Materials Crystallizationmentioning
confidence: 93%
“…Zainorabidin & Mohamad [26] found that differences in moisture content existed and were influenced by a variety of factors, including variations in groundwater level at the location and undrained forest conditions. These differences in results are attributable to climate change because of changes in temperature, precipitation, and rainfall impacting soil saturation intensity, where the water table forms in a roughly horizontal plane and may rise to a level larger or less than the actual water table [29]. Furthermore, particle size has an impact on moisture content.…”
Section: Index Properties Of Klias Beaufort Peat Soil (Kbpt)mentioning
confidence: 99%
“…At this stage, cyclic shear strains would lead to strain softening, particle structure breakdown and a rapid deterioration of stress-strain-shear strength characteristics up to the plastic threshold. It is known that peat soil is highly compressible [36] thus, the compressible behaviour of peat soil seen as the major causes to the changes in shear strength which in line with the statement where peat is soft and easily compressed when load imposed [37].…”
Section: Dynamic Loading Characteristics Based On Cyclic Triaxial Testmentioning
confidence: 59%
“…The post-cyclic yield shear strength of undisturbed peat soil is considerably lower compared to static while cyclic loading is imposed to specimens after 100 numbers of cycles. The initial stiffness of post-cyclic for peat soil is governed by the softening behaviour that occurred when the specimen exhibited ± 1.5% axial strain [32,36]. However, peat still showing the peculiarities behaviour consistently that showed, peat is not easy to handle and yet, challenging to the author.…”
Section: Figure 7 Relationship Between Maximum Strain Due To Cyclic L...mentioning
confidence: 99%